Clinical Outcome of Children With Antenatally Diagnosed Hydronephrosis - Chiodini, Benedetta; Ghassemi, Mehran; Khelif, Karim; Ismaili, Khalid (Frontiers in Pediatrics, 2019)
Fetal renal pelvis dilation is a common condition, which is observed in 1 to 4.5% of pregnancies. In many cases, this finding resolves spontaneously. However, sometimes it may be a signal of significant urinary tract pathologies. The main abnormalities found after birth are uretero-pelvic junction stenosis, primary vesicoureteral reflux, megaureter, duplex kidneys, and posterior urethral valves, with uretero-pelvic junction stenosis and primary vesicoureteral reflux accounting for most of the cases. Diagnosis, management, and prognosis at short and longer term of these conditions will be reviewed in this article.